“To steel the heart against itself”: The Influence of Byron on Emily Brontë - Quinnell, James (Romanticism on the Net, 2020)
I argue that the influence of Byron on Emily Brontë’s poetry is far more nuanced than is sometimes recognised in scholarly discussion. Consideration of the ways in which Byron shaped Emily Brontë as a writer is often in thrall to notions of the byronic. Thus, Byron becomes a way of accounting for Emily’s supposed preference for the outsider and privileging of intense emotional states. Through focussing on Childe Harold’s Pilgrimage, particularly the third canto, I argue that Byron is present in Emily Brontë’s moments of emotional restraint. Far from being, to use Andrew Elfenbein’s phrase, “an early chapter in the bildungsroman of the Victorian author,” Byron shapes Emily Brontë’s mature consideration, in her later poetry, of the pitfalls inherent in an abandonment to emotional intensity. Byron taught Emily Brontë, to use his own words from Childe Harold’s Pilgrimage, to “think less wildly.” Byron’s poetry of emotional stress such as Childe Harold’s Pilgrimage and Manfred is quite rightly heard in Emily Brontë’s writing; however, in the second half, I discuss how Byron’s more satirical voice is also heard. I use Don Juan to explore how Brontë’s reading of Byron may have helped her to, again using Byron’s phrase, “ponder boldly.” So, Byron helps to shape Emily Brontë’s stoicism and philosophical detachment. Throughout the article, my thinking is alive to the different and, at times, competing Romantic voices that make themselves heard in Emily Brontë’s poetry; however, my main aim is to enrich understanding of the different ways in which Byron’s voice is heard.